Major Adverse Cardiovascular Events and Cause-Specific Mortality After Hospitalisation in COPD - Ioannides AE; Whittaker HR; Quint JK (International Journal of COPD, 2025)
Anne E Ioannides, Hannah R Whittaker, Jennifer K Quint School of Public Health (SPH), White City Campus, Imperial College London, London, UKCorrespondence: Anne E Ioannides, School of Public Health (SPH), White City Campus, Imperial College London, 90 Wood Lane, London, W12 0BZ, UK, Email a.ioannides@imperial.ac.ukPurpose: People with chronic obstructive pulmonary disease (COPD) are at elevated risk of cardiovascular events and mortality. We aimed to determine, in a COPD population, the relationship between hospitalization and post-discharge one-year rates of (i) major adverse cardiovascular events (MACE) and (ii) cause-specific mortality.Patients and Methods: We conducted a prospective cohort study on a COPD population, between 01/01/2010 and 31/12/2019, using nationally-representative, routinely collected electronic healthcare records in England (Clinical Practice Research Datalink Aurum primary care data, linked with secondary care [Hospital Episode Statistics], and mortality [Office of National Statistics] data). The exposure was ≥one hospitalization, and the control group was no hospitalization. Outcomes were one-year rates of (i) non-fatal MACE (acute coronary syndrome, arrhythmia, heart failure, or ischemic stroke) and (ii) cause-specific mortality. Exposures were stratified by hospitalization type (elective and emergency) and cause (all-cause, cardiovascular, respiratory, and non-cardiorespiratory). We implemented adjusted Cox proportional hazard regression models, and sensitivity doubly robust propensity score-adjusted models.Results: Hospitalized COPD patients had significantly higher rates (incidence rate [IR, per 1000 person-years]; adjusted hazard ratio {aHR} [95% confidence interval {95% CI}] of MACE in the year following hospitalization, whether elective (IR=33.3; 7.04 [6.19– 8.07]) or emergency (IR=70.0; 8.85 [7.78– 10.06]), versus those without hospitalization (IR=3.4). Emergency hospitalization was associated with increased all-cause mortality (IR=146.5; 2.49 [2.37– 2.61]), regardless of hospitalization cause, compared to those not hospitalized (IR=30.3). Elective hospitalization was also associated with increased all-cause mortality (IR=54.6; 1.32 [1.25– 1.38]), except for cardiovascular elective hospitalization (1.00 [0.89– 1.12]). Cause-specific mortality was influenced largely by hospitalization cause.Conclusion: Hospitalized COPD patients experienced increased subsequent one-year MACE and mortality rates, regardless of hospitalization cause or type. Hospitalization for any reason in COPD patients provides an opportunity to provide primary prevention for MACE.Keywords: COPD, MACE, cause-specific mortality, hospitalization